(untitled) (Journal of Medical & Health Sciences Review, 2025)
Mulberry (Morus spp.), including M. alba, M. nigra and M. rubra, is a healthful and medicinal fruit that has been used for a long time in traditional medicine. Even though cherries are rich in antioxidants, anthocyanins, flavonoids and phenolic compounds, their limited usage in industry is caused by how quickly they spoil and because all processing methods are not standardized. In this review, we study what mulberry fruit and leaves are made of, how they benefit health and how they are extracted, putting special emphasis on bioactive compounds. Many techniques, enzyme-assisted, ultrasound-assisted, microwave-assisted and high-speed shear homogenization, have been investigated to see if they can boost bioactive compound yield and keep them stable. Moreover, the work focuses on microencapsulation and functional foods, showing how it can lead to better antioxidant absorption, better digestion and advantages for diabetes, heart disease, brain health and cancer. The results highlight the need for new processing technologies to make mulberry a reliable and useful source of nutrients in the nutraceutical and food fields.